Pembuatan Gum Xanthan dengan Proses Fermentasi dari Hidrolisat Selulosa Eceng Gondok dan Penerapannya dalam Enhanced Oil Recovery - Ramadhan, Handi; Arif Dharmawan, Wahyu; Susilowati, Titi (Jurnal Teknik Kimia USU, 2023)
Water hyacinth is a freshwater plant that has a negative impact on waters, but has a high cellulose content (77.6%) and is still underutilized. One alternative in controlling the amount of water hyacinth is to utilize its potential cellulose content as an ingredient in xanthan gum. Fermentation was carried out with the help of Xanthomonas campestris and xanthan gum was obtained, which can be used as a polymer injection material to increase crude oil production in the oil refinery industry. The stages to obtain xanthan gum are delignification, hydrolysis, and anaerobic fermentation (28 °C) with a time variation of 24 hours to 120 hours with an interval of 24 hours. The cellulose hydrolysate variable is 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%. The yield of xanthan gum in this research was 18%, with a moisture content was 13% – 15% and an ash content was 3% –3.9%. The resulting xanthan gum was analyzed for its functional groups using Fourier Transform Infra Red (FTIR) and was in agreement with commercial xathan gum.